KOMBINASI DAUN GAMAL (Gliricidia sepium) DAN DAUN PAPAYA (Carica papaya) DALAM RANSUM TERNAK KAMBING KACANG (Combination of gamal (Gliricidia sepium) and papaya (Carica papaya) leaves in ration supplement of kacang goat) - Emma D. Wie Lawa; Edwin J. L. Lazarus; Maritje A. Hila Kore (JURNAL NUKLEUS PETERNAKAN, 2021)
This study examined the effect of the use of gliricidia leaves and papaya leaves in rations on the growth of kacang goats. The male Kacang goat, growth age (1 - 1.5 years) as many as 12 tails with an initial body weight of 13.55 ± 0.036 kg (BW ± standard error) were used as experimental animals. The experimental design used is a complete randomized design of factorial patterns 2 x 2 with two factors, namely, gliricidia leaf factor (A) with two levels of giving (a1 15% and a2 30%), papaya leaf factor (B) with two levels of giving (b1 5% and b2 10%) so that 4 treatment combinations are formed. The combination of treatments is, a1b1, a1b2, a2b1 and a2b2. The treatment was repeated 3 times to form 12 experimental units. The parameters tested were the consumption and digesting of dry matter as well as ration nutrients, weight gain and efficiency of ration use. The data was analyzed using analysis of variance (ANOVA) and followed by the Duncan test to compare between treatments. The results showed that there was no significant interaction (P >0.05) on all the parameters measured. The response of goat to parameters is more influenced by the single effect of gliricidia leaves and papaya leaves. The response to the use of gliricidia leaves is 30% and papaya leaves are 10% higher than the level of use below. It was concluded that the use of gliricidia leaves and papaya leaves can increase goat growth but the combination has not provided a significant interaction for it requires further study with a combination of higher levels.